(untitled) (Journal of Economic Research & Business Administration, 2015)
Modern industry, being part and parcel of the economy consists of many independent industries, each of which includes a large group of related enterprises and production units located in some cases signifi cant territorial distance from each other. Composition and structure of production industry is important for the economy of the state, thereby predetermining economic strength and independence of the state. Research into the causes, the nature and patterns of structural adjustment allows you to create a solid foundation to develop the strategy and tactics of practical action for the implementation of structural changes, as well as to form, resulting in the transformation of production relations, the mechanism of regulation of this process, contributing to the country’s exit from the crisis and the establishment of a competitive economy. Industry is largely determining the sector of the national economy. Analysis of the state of the industry shows that currently the main problems of development is unsustainable, a slowdown in the previous years, the most important indicators of a decrease in production effi ciency, slow improvement in the structure of industrial production and exports, the high cost of resources.